Low optical losses in plasmonic TiN thin films implanted with silver and gold - Novakovic, Mirjana; Popovic, M.; Noga, Pavol; Vana, D.; Ronning, Carsten (Optical Materials, 2022)
Titanium-nitride (TiN) is known as a very promising plasmonic material, which offers many advantages compared to conventional metals commonly used in practical devices. Despite many improvements, TiN still suffers from high losses in the near-infrared (NIR) spectral region, making it less suitable for real-life applications. In this study, we have investigated the effects of pure silver implanted as well as silver/gold co-implanted TiN thin films on their optical properties, which we analyzed by spectroscopic ellipsometry. We demonstrate that the presence of silver and gold drastically changes both the real and imaginary part of the dielectric function. The implanted films exhibit optical losses several times lower compared to as-deposited TiN. The changes are in particular more pronounced for the samples with Au/Ag co-implantations, reaching nearly the same optical values as those of pure gold and being only slightly larger than that of silver. Thus, such an optical tuning of TiN opens new horizons and provide high potential for its implementation into plasmonic applications.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Gold; Ion implantation; Optical losses; Plasmonics; Silver; Titanium-nitride